Black Soldier Fly Larvae Frass Production for Managing Water Hyacinth Encroachment - Mohd Hasyrin, Hassan; Latifah, Omar; Ahmed Osumanu, Haruna; Ng, Ji Feng; Mugunthan, Perumal; Muhammad Huzaifah, Mohd Roslim (International Journal of Agricultural, Forestry & Plantation (IJAFP), 2023)
Water hyacinth (WH) is one of the most invasive and toxic aquatic weeds which detrimentally affects freshwater quality and ecosystem via hindering sunlight from reaching aphotic zone and depleting oxygen level in water bodies. Black soldier fly larvae (BSFL) as degradation agent that feed on WH is an approach to manage the invasive plant. The objectives of this study were to: (i) produce frass from BSFL which is mature and suitable for improving soil and seed germination by using WH as feeding substrates and (ii) characterize the agronomic properties of the frass produced from BSFL after being fed on WH. The frass production was carried out by rearing BSFL using WH at a feeding rate of 200 mg larvae-1 day1 for 48 days. The rearing of BSFL using WH was carried out and monitored for the changes of BSFL to pupae. Water hyacinth was fully digested by BSFL at 48 days. The BSFL frass were sieved to pass a 2 mm sieve and characterized for the physical, biological, and chemical properties. The BSFL colour was dark, and the odour became earthy, suggesting that the frass had reached maturity. The BSFL frass resulted in 100% germination and showed 86.46% germination index of maize seeds in frass produced from WH revealing that the frass had no toxic effect, but rather promoted seedling growth. The BSFL frass is a slightly alkaline material (pH =7.64), and its electrical conductivity (6 µS/cm) was in the range of permissible level as an organic fertilizer. The BSFL frass could be considered as an organic fertilizer with an appropriate range of organic matter (50.31%), organic carbon (29.18%), 2.18% total N, 1270 mg kg-1 ammonium, 1370 mg kg-1 and nitrate. The C/N ratio of BSFL frass was 13 suggesting that the frass can decompose rapidly to release essential nutrients for crop uptake. The BSFL frass produced from WH has potential to be used as organic fertilizer to promote crop growth and soil productivity. A pot experiment study is in progress to determine the effects of BSFL frass on soil productivity and crop growth.